Kecemasan Orang Tua pada Anak Autisme - I Nengah Sumirta (Jurnal Gema Keperawatan, 2013)
The purpose of this research is to know about the level of anxiety of parents who has autism children. The type of the research used in this research is a descriptive research plan with cross sectional approaching. The result of research which is done in school for disable A Tuna Netra Denpasar got the data, it is most of the samples are 22-39 years old as much as 53% and majority of respondents is a female as much as 75%. The level of education which is dominated is a middle level of education as much as 59%, whereas type of job which is dominated is entrepreneur as much as 66%. The result is showing the most of the respondents feels the middle of anxiety level as much as 56%